GINGIVAL TISSUE IL-1beta AND PGE2 LEVELS IN PATIENTS WITH CHRONIC PERIODONTITIS AFTER ADDITIONAL THERAPY WITH NON-STEROIDAL ANTI-INFLAMMATORY DRUGS - Christina Popova; Antoaneta Mlachkova (Peytchinski Publishing, 2010)
Background: The understanding of the pathogenesis of periodontitis makes various progresses in the last decades. Today it is well known that the synthesis of high levels of pro-inflammatory mediators from gingival tissues in response to periodontopathogens results in destruction of soft and hard periodontal tissues and clinical expression of periodontal disease. There is enough evidence that PGE2 and IL-1beta are important mediators in the initiation and progression of periodontal disease. Detection of numerous cytokines in high levels in gingival tissues and crevicular fluid may be indicator for activity of periodontitis. The reduction of IL-1beta and PGE2 levels after periodontal therapy may be a potential criterion for successful periodontal therapy. The occurrence of increased IL-1beta and PGE2 levels in GCF or gingival tissue is able to indicate risk from progression of destruction in specific periodontital site. The current conception of the pathogenesis of periodontitis suggests that additional host modulation approach may inhibit the production of pro-inflammatory mediators in periodontal tissues and may enhance the treatment result. Aim of the study: To evaluate the effectiveness of additional host modulation therapy with NSAID (Aulin®) in non-surgical therapy of chronic periodontitis by measurement of IL-1beta and PGE2 gene expression levels in patient's gingival tissues. Materials and methods: Evaluation of prostaglandin E2 (PGE2) and interleukin-1beta (IL-1beta) gene expression levels in gingival tissue of chronic periodontitis patients before and after non-surgical periodontal therapy (scaling and root planing) was performed. Prostaglandin E2 (PGE2) and interleukin-1beta (IL-1beta) gene expression levels in gingival tissue of patients with chronic periodontitis receiving conventional mechanical therapy alone or with additional host modulation therapy with NSAID (Aulin®) - 100 mg per day were compared. PCR analysis- TagMan RT-PCR for evaluation of gene expression levels of IL-1beta and PGE2 in gingival tissue of periodontal patients was applied. Results: Statistically significant differences were found between additional Aulin® therapy group and conventional therapy group. Received correlative coefficient with Spearman analysis was respectively t = -0.72 (p< 0,05) for IL-1beta and t = 0.81(p<0,05) for PGE2. The negative values of ddCt in test group reveal lower level of inhibition of gene expression. The comparative analysis of the collected data demonstrates fewer differences between both groups. The deviations in gene expression levels of IL -1beta and PGE2 are higher in the patients treated with adjunctive medication with Aulin®. Conclusion: This study confirms the effectiveness of non-surgical therapy in moderate and severe periodontitis. Additional use of non-steroidal anti-inflammatory agent Aulin® results in higher inhibition of the pro-inflammatory cytokines IL-1beta and PGE2. This data may be the base for modifying the conventional non-surgical therapy by including anti-inflammatory agents in the treatment of chronic periodontitis.